LANGUAGE ACQUISITION IN CHILDHOOD STAGE: A REVIEW - Budiharso, Teguh (Center of Language and Cultural Studies [CLCS], 2019)
This paper reviews the language acquisition theory in childhood stages. Five models of baby’s language development including pre-linguistic, holophrastic, telegraphic, simple sentence, and compound sentence are central of discussion. In the early stage, characteristics of language development and language learning in the kindergarten level are discussed integratedly. In the area of Second Language Acquisition (SLA), Krashen Theory in Natural Approach is prevalent, prevailing frontier concepts in children language development. In the social context, language view that has closed relationship to culture is included. This way, norm, etiquette, values, and other aspects of communication are valuable to teaching children in the early stage.